A comparison of control strategies for wave energy converters. (December 2017) - Coe, Ryan G.; Bacelli, Giorgio; Wilson, David G.; Abdelkhalik, Ossama; Korde, Umesh A.; Robinett III, Rush D.
Highlights: Eight power take-off control strategies are considered for a wave energy converter. Controllers are used to conduct simulations with a reduced order dynamics model. Statistical metrics are compiled to track relative performance of each controller. A comparison across strategies shows large variation in power absorption. Each controller has unique requirements which must be met for implementation. Abstract: In this study, we employ a numerical model to compare the performance of a number of wave energy converter control strategies. The controllers selected for evaluation span a wide range in their requirements for implementation. Each control strategy is evaluated using a single numerical model with a set of sea states to represent a deployment site off the coast of Newport, OR. A number of metrics, ranging from power absorption to kinematics, are employed to provide a comparison of each control strategy's performance that accounts for both relative benefits and costs. The results show a wide range of performances from the different controllers and highlight the need for a holistic design approach which considers control design as a parallel component within the larger process WEC design.